Transformation of Educational Practice: The Role of Organizational Learning in Teacher Professional Development - De La Torre Figueroa, Erika Mariuxi (2024)
The objective of this study was to investigate the correlation of organizational learning on the professional development of teachers in an educational unit in Guayaquil, Ecuador. The methodology used was quantitative, non-experimental and correlational in scope, with a sample of 100 teachers. Cronbach's alpha was used to validate the data collection instruments, obtaining high reliability indexes, and chi-square was used to evaluate the independence between categorical variables and to determine the significant association between them. The results showed that organizational learning has a significant impact on teacher professional development, with the associated significance values (Sig.) being 0.021 for Pearson and 0.032 for Deviance. It is concluded that implementing effective organizational learning strategies can substantially improve teachers' professional development and, consequently, educational quality.